Determination of Tractor Engine Oil Change Interval Based on Material Properties - Hönig, Vladimír; Procházka, Petr; Obergruber, Michal; Kučerová, Viera; Mejstřík, Pavel; Macků, Jan; Bouček, Jiří (Materials (Basel, Switzerland), 2020)
This article focuses on the issue of motor oils used in the engines of non-road mobile machinery (NRMM), more specifically tractors. The primary goal of the paper is to determine the appropriate replacement interval for these oils. The physical properties of the examined samples were first determined by conventional instruments. Furthermore, the concentrations of abrasive metals, contaminants, and additive elements were measured using an optical emission spectrometer. Lastly, the content of water, fuel, and glycol and the products of oxidation, nitration, and sulfation were determined by using infrared spectrometry. The measured values were compared to the limit values. Based on the processing and evaluation of these analyses, the overall condition of the oils was assessed and subsequently the optimal exchange interval of the examined oils was determined. In addition, a risk analysis of the outage was performed. Due to the high yields of crops, farmers can lose a significant amount of product when a tractor is not functioning during the harvest period. This loss is calculated in the paper.
Keywords: engine oil; wear out; oil change interval; risk analysis; tribotechnical diagnostics